Answer:
See the proof below.
Step-by-step explanation:
Assuming this complete question: "For each given p, let Z have a binomial distribution with parameters p and N. Suppose that N is itself binomially distributed with parameters q and M. Formulate Z as a random sum and show that Z has a binomial distribution with parameters pq and M."
Solution to the problem
For this case we can assume that we have N independent variables
with the following distribution:
bernoulli on this case with probability of success p, and all the N variables are independent distributed. We can define the random variable Z like this:
From the info given we know that
We need to proof that
by the definition of binomial random variable then we need to show that:
![E(Z) = Mpq](https://tex.z-dn.net/?f=%20E%28Z%29%20%3D%20Mpq)
![Var (Z) = Mpq(1-pq)](https://tex.z-dn.net/?f=%20Var%20%28Z%29%20%3D%20Mpq%281-pq%29)
The deduction is based on the definition of independent random variables, we can do this:
![E(Z) = E(N) E(X) = Mq (p)= Mpq](https://tex.z-dn.net/?f=%20E%28Z%29%20%3D%20E%28N%29%20E%28X%29%20%3D%20Mq%20%28p%29%3D%20Mpq)
And for the variance of Z we can do this:
![Var(Z)_ = E(N) Var(X) + Var (N) [E(X)]^2](https://tex.z-dn.net/?f=%20Var%28Z%29_%20%3D%20E%28N%29%20Var%28X%29%20%2B%20Var%20%28N%29%20%5BE%28X%29%5D%5E2%20)
![Var(Z) =Mpq [p(1-p)] + Mq(1-q) p^2](https://tex.z-dn.net/?f=%20Var%28Z%29%20%3DMpq%20%5Bp%281-p%29%5D%20%2B%20Mq%281-q%29%20p%5E2)
And if we take common factor
we got:
![Var(Z) =Mpq [(1-p) + (1-q)p]= Mpq[1-p +p-pq]= Mpq[1-pq]](https://tex.z-dn.net/?f=%20Var%28Z%29%20%3DMpq%20%5B%281-p%29%20%2B%20%281-q%29p%5D%3D%20Mpq%5B1-p%20%2Bp-pq%5D%3D%20Mpq%5B1-pq%5D)
And as we can see then we can conclude that ![Z \sim Bin (M, pq)](https://tex.z-dn.net/?f=%20Z%20%5Csim%20Bin%20%28M%2C%20pq%29)
Answer:
A
Step-by-step explanation:
A is the procedure
![3(5x - 4) - (-30-45x)](https://tex.z-dn.net/?f=3%285x%20-%204%29%20-%20%28-30-45x%29)
![= 15x - 12 + 30 + 45x](https://tex.z-dn.net/?f=%3D%2015x%20-%2012%20%2B%2030%20%2B%2045x)
<- Distributive Property
![=60x + 18](https://tex.z-dn.net/?f=%3D60x%20%2B%2018)
<- Combine Like Terms
If you're trying to solve for 0:
![0 = 60 x + 18](https://tex.z-dn.net/?f=0%20%3D%2060%20x%20%2B%2018)
![-18 = 60x](https://tex.z-dn.net/?f=-18%20%3D%2060x)
<- Subtracted 18 from both sides
![x = \frac{-18}{60} = \frac{-9}{30}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-18%7D%7B60%7D%20%3D%20%5Cfrac%7B-9%7D%7B30%7D)
<- Divided both sides by 60 and then simplified.
![x = \frac{-9}{30}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-9%7D%7B30%7D)
<- Fraction Form
![x = -0.3](https://tex.z-dn.net/?f=x%20%3D%20-0.3)
<- Decimal Form
Give Brainliest for simple answer plz :P
Answer:
4
Step-by-step explanation:
Answer:
x = 3; y = -6
Step-by-step explanation:
x - 2y = 15
2x + 4y = -18
Multiply both sides of the first equation by 2. Write the second equation below it, and add the two equations.
2x - 4y = 30
(+) 2x + 4y = -18
---------------------------
4x = 12
4x/4 = 12/4
x = 3
Now we substitute 3 for x in the first equation and solve for y.
x - 2y = 15
3 - 2y = 15
-2y = 12
y = -6
Answer: x = 3; y = -6